A Combined Cosmogenic Nuclides Approach for Determining the Temperature‐Dependence of Erosion - Dennis, Donovan P.; Scherler, Dirk; Scherler, Dirk; 1 Helmholtz Centre Potsdam GFZ German Research Centre for Geosciences Potsdam Germany (Journal of Geophysical Research: Earth Surface, 2022)
Physical weathering in cold, steep bedrock hillslopes occurs at rates that are thought to depend on temperature, but our ability to quantify the temperature‐dependence of erosion remains limited when integrating over geomorphic timescales. Here, we present results from a 1D numerical model of in‐situ cosmogenic 10Be, 14C, and 3He concentrations that evolve as a function of erosion rate, erosion style, and ground surface temperature. We used the model to explore the suitability of these nuclides for quantifying erosion rates in areas undergoing non‐steady state erosion, as well as the relationship between bedrock temperature, erosion rate, and erosional stochasticity. Our results suggest that even in stochastically eroding settings, 10Be‐derived erosion rates of amalgamated samples can be used to estimate long‐term erosion rates, but infrequent large events can lead to bias. The ratio of 14C to 10Be can be used to evaluate erosional stochasticity, and to determine the offset between an apparent 10Be‐derived erosion rate and the long‐term rate. Finally, the concentration of 3He relative to that of 10Be, and the paleothermometric interpretations derived from it, are unaffected by erosional stochasticity. These findings, discussed in the context of bedrock hillslopes in mountainous regions, indicate that the 10Be‐14C‐3He system in quartz offers a method to evaluate the temperature‐sensitivity of bedrock erosion rates in cold, high‐alpine environments. Plain Language Summary: All mountains erode, but not all mountains erode in the same way and at the same rate. In cold mountainous landscapes, temperature is thought to be an important control on erosion. Previous research suggests that rocks fracture by frost most effectively at temperatures between −3°C and −8°C, and that the warming and thawing of permanently frozen ground (permafrost) destabilizes hillslopes and leads to more and larger rockfalls. However, our ability to test these hypotheses is limited, due to difficulties in measuring or estimating erosion ...